2020
DOI: 10.3390/en13010265
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Dynamics Study of the Generation of Ethanol for Insulating Paper Pyrolysis

Abstract: Cellulosic insulation paper is usually used in oil-immersed transformer insulation systems. In this study, the molecular dynamics method based on reaction force field (ReaxFF) was used to simulate the pyrolysis process of a cellobiose molecular model. Through a series of ReaxFF- Molecular Dynamics (MD) simulations, the generation path of ethanol at the atomic level was studied. Because the molecular system has hydrogen bonding, force-bias Monte Carlo (fbMC) is mixed into ReaxFF to reduce the cost of calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Molecular dynamics plays an irreplaceable role in discovering new phenomena and clarifying new mechanisms [62]. Zhang's research group [63] used the molecular dynamics method based on reaction force field (ReaxFF) modules of Amsterdam Modelling Suite (AMS) software to simulate the pyrolysis process of cellobiose. A model composed of 40 cellobiose is established, and the simulation temperature is 500 to 3000 K. In order to make ReaxFF closer to the actual situation and ensure reliability, the force‐biased Monte Carlo method is introduced into ReaxFF.…”
Section: Formation Mechanism Of Methanolmentioning
confidence: 99%
“…Molecular dynamics plays an irreplaceable role in discovering new phenomena and clarifying new mechanisms [62]. Zhang's research group [63] used the molecular dynamics method based on reaction force field (ReaxFF) modules of Amsterdam Modelling Suite (AMS) software to simulate the pyrolysis process of cellobiose. A model composed of 40 cellobiose is established, and the simulation temperature is 500 to 3000 K. In order to make ReaxFF closer to the actual situation and ensure reliability, the force‐biased Monte Carlo method is introduced into ReaxFF.…”
Section: Formation Mechanism Of Methanolmentioning
confidence: 99%
“…It was found that cellulose chains with different DPv have the same molecular conformation and physical and chemical properties. Thus, the repeating unit of the cellulose chain (cellobiose molecule) was used as the simulation model with the consideration of computational power and efficiency [31], as shown in Fig. 1.…”
Section: Construction Of Cellulose Modelmentioning
confidence: 99%
“…Based on the TAD theory, the temperature of 1600 K, 1800 K, and 2000 K was set to investigate the formation mechanisms. Besides, Zhang et al used the same assumptions and conditions for the cellulose model to study the reaction mechanism of methanol [38] and ethanol [31].…”
Section: Figure 1 Chemical Formula and Molecular Model Of Cellobiosementioning
confidence: 99%
“…By the way the efficiency of impurities removal obtained with a decline of 14% of polar substances and 32% of oxides in polymer organic membranes applications. The advantages of employing the ultrasonic separation technology refer to wide and continuous applications, high efficiency, low contact, and low pollution but it demands a microfluidic chip and acoustic radiation force (generator) [57][58][59][60][61][62][63][64].…”
Section: Plasma Technology and Recent Developmentsmentioning
confidence: 99%